The History of Historical Science. A Normative Story of One´s Own Field or a Reflexive History of Cultural Praxis? On the Collection German Medieval Studies in the Czech Lands up to 1945 - Kolář, Pavel (Dějiny – teorie – kritika, 2024)
This polemic article is a reaction to the collection Německá medievistika v českých zemích do roku 1945 / German Medieval Studies in the Czech Lands up to 1945. In it the author considers contemporary Czech scholarship on German historiography of the end of the 19th and first half of the 20th century and criticises the methodologically unexplained limitation of the work to medieval studies. He argues against the rigid division of German historiography into university and regional and the unambiguous definition of economic and social history as the matrix for distinguishing between two German historiographies. From the methodological point of view he challenges the use of almost any kind of normative assumptions when writing the history of historiography. He regards the best research approaches to be those that use biographical analysis to uncover the strategic practice of specific historians. Conversely he questions studies concerned with identifying the contribution of Germans historians to the crimes of Nazism and its legitimisation, and takes a sceptical view of the possibility of distinguishing between ideological "deformation" and "pure scholarship".